IBM Cloud Object Storage System product guide - Gucer, Vasfi; Almeida, Chris de; Dorio, Joe; Feygelman, Israel; Huber, Max; Knieriemen, Michael; Lauber, Lars; Lehtinen, Jussi; Saini, Jaswinder Singh (IBM Redbooks, 2023)
Object storage is the primary storage solution that is used in the cloud and on-premises solutions as a central storage platform for unstructured data. IBM Cloud Object Storage is a software-defined storage (SDS) platform that breaks down barriers for storing massive amounts of data by optimizing the placement of data on commodity x86 servers across the enterprise. This IBM Redbooks® publication describes the major features, use case scenarios, deployment options, configuration details, initial customization, performance, and scalability considerations of IBM Cloud Object Storage on-premises offering. For more information about the IBM Cloud Object Storage architecture and technology that is behind the product, see IBM Cloud Object Storage Concepts and Architecture , REDP-5537. The target audience for this publication is IBM Cloud Object Storage IT specialists and storage administrators.